2021
DOI: 10.1108/jwl-04-2020-0067
|View full text |Cite
|
Sign up to set email alerts
|

Impact of professionalism of workplace learning support team on learning outcome

Abstract: Purpose This study aims to understand the impact of professionalism (PR) of the workplace learning support team on learning outcomes. The context of this study is an e-procurement system implementation. Management provides initial formal training (TR) to potential users of the system and also arranges informal learning support by deploying the support team for technical guidance/resolving issues on day-to-day basis for successful implementation. Learning outcome has been measured in terms of perceived ease of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…This can be further demonstrated on the results of the study of Kumar and Ganguly (2021) that revealed that professionalism of the workplace learning support team has positive effect on the employee's perception of ease of actual using the e-procurement system implementation. "The study also found that the employee's perceived ease of using the system mediates the relationship between the professionalism of the workplace learning support team and the actual use of the system."…”
Section: International Journal Of Research Studies In Management 131mentioning
confidence: 89%
“…This can be further demonstrated on the results of the study of Kumar and Ganguly (2021) that revealed that professionalism of the workplace learning support team has positive effect on the employee's perception of ease of actual using the e-procurement system implementation. "The study also found that the employee's perceived ease of using the system mediates the relationship between the professionalism of the workplace learning support team and the actual use of the system."…”
Section: International Journal Of Research Studies In Management 131mentioning
confidence: 89%
“…It is more of a socially constructed and contextual variable; it relates to the requirements imposed on employees to perform certain duties (Troman, 1996). This means that as society changes, the criteria by which the practical performance of professionals is assessed also change, and new improvement and learning outcomes are defined (Kumar & Ganguly, 2021) to meet the collective demands of organization and society.…”
Section: Previous Findingsmentioning
confidence: 99%
“…Specifically, Islam and Ahmed (2018) emphasized the importance of workplace support (an organizational factor) towards employees' psychological well-being. Workplace support is an interpersonal transaction of help from colleagues that involve emotions, information and material assistance (Hombrados-Mendieta and Cosano-Rivas, 2013); nonetheless, this type of support hinder individual’s need of being valued and acknowledgement by their organization (Kumar and Ganguly, 2021). Therefore, we extend literature by investigating the conditional role of perceived organizational support (POS) towards psychological well-being.…”
Section: Introductionmentioning
confidence: 99%